The Modernisazion of Reflection on Ar-Raisuni Thought In The Islamic Family Law Of Indonesia: THE MODERNISAZION OF REFLECTION ON AR-RAISUNI THOUGHT IN THE ISLAMIC FAMILY LAW OF INDONESIA - Tutik Hamidah Hamidah; Abbas Arfan Arfan; Irma Nur Hayati Hayati (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2022)
Abstract: The development of today's era requires Muslims to be able to filter the information circulating in the community to be able to examine its truth based on the sources of the Qur'an and hadith. Meanwhile, the paradigm related to Islamic law in Indonesia must have clear shari'ah and creed boundaries. So that it does not cause controversy for Muslims. This paper discusses the perspective of Ar-Raisuni's reflection in Islamic family law in Indonesia. The type of research used is Library Research, by providing data analysis from various sources, both from scientific journals, online news or books. The problems faced are problems in the context of Islamic family law in Indonesia which are studied from the perspective of Ar-Raisuni. The conclusion of this paper provides an understanding that, Islamic law has a function as